2018
DOI: 10.1002/casp.2389
|View full text |Cite
|
Sign up to set email alerts
|

How Palestinian students invoke the category “human” to challenge negative treatment and media representations

Abstract: Dehumanisation of opponents in conflict has been shown to be a common and damaging feature in the media. What is not understood is how this dehumanisation is challenged, which is the novel contribution that this research will make. Drawing on focus groups (four focus groups each with four to six participants) conducted in the West Bank in 2015 that discussed media coverage of international conflict, this article demonstrates the ways in which young Palestinian participants attempt to rehumanize themselves in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
1
4
0
1
Order By: Relevance
“…This is consistent with previous research showing that being recognized in terms of human values predicted better outcomes for intergroup relations, including trust and forgiveness, which appeared beyond the effect of feeling liked by the outgroup (Livingstone et al, 2019). These patterns of findings are also consistent with qualitative research suggesting that being part of the human category is very important, because it can encourage people to see that there are still genuine people among members of outgroups (Heywood & Goodman, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with previous research showing that being recognized in terms of human values predicted better outcomes for intergroup relations, including trust and forgiveness, which appeared beyond the effect of feeling liked by the outgroup (Livingstone et al, 2019). These patterns of findings are also consistent with qualitative research suggesting that being part of the human category is very important, because it can encourage people to see that there are still genuine people among members of outgroups (Heywood & Goodman, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…Research at an interpersonal level has shown that people dehumanize those who they perceive to dehumanize them (e.g., Bastian & Haslam, 2010. At the intergroup level, when people perceive that outgroup members dehumanize their own ingroup (i.e., metadehumanization), they become motivated to humanize the ingroup (Heywood & Goodman, 2019) and to reciprocally dehumanize and show hostility towards the offending outgroup (Kteily, Hodson, & Bruneau, 2016). Moreover, the effects of metadehumanization have been shown to be distinct from the effects of perceiving that outgroup members dislike one's ingroup (i.e., meta-prejudice: Kteily et al, 2016).…”
mentioning
confidence: 99%
“…In contexts marked by intergroup intractability, the perception of outgroup members' humanity is one of the important facets of achieving reconciliation (Andrighetto, Mari, Volpato, & Behluli, 2012;Bar-Tal, 2000). Members of victim groups need to not only rehumanize their ingroup but also believe that decent people with genuine intentions are among their current and/or former adversaries (Heywood & Goodman, 2019). Enabling them to consider former opponents as fully human may be necessary for their positive understanding of that outgroup's prosocial and emotional actions and/or intentions.…”
Section: The Mediating Role Of Perceived Outgroup Humannessmentioning
confidence: 99%
“…Niekiedy zmniejszanie wrogości polega na przyjęciu innego sposobu myślenia o grupach (np. konflikt w Rwandzie jako spór Rwandyjczyków z Rwandyjczykami, a nie Hutu z Tutsi 82 ), podkreślaniu wspólnego losu 83 czy człowieczeństwa wszystkich stron 84 . W Rwandzie obok narzędzi "oficjalnych", w tym trybunałów powołanych do osądzenia zbrodniarzy, wykorzystywano także tradycyjne zgromadzenia, wiece (Gacaca) i to one mogły decydować o sprawach "mniejszego kalibru", na przykład o przemocy, które nie uznano za przejaw ludobójstwa lub przestępstw przeciwko mieniu.…”
Section: "Mniej Niż Ludzie" Czyli O Dehumanizacji I Rehumanizacji W "...unclassified